2014
DOI: 10.1137/130947878
|View full text |Cite
|
Sign up to set email alerts
|

On the Number of Graphs Without Large Cliques

Abstract: In 1976 Erdős, Kleitman and Rothschild determined the number of graphs without a clique of size ℓ. In this note we extend their result to the case of forbidden cliques of increasing size. More precisely we prove that for ℓn ≤ (log n) 1/4 /2 there are 2 (1−1/(ℓn−1))n 2 /2+o(n 2 /ℓn) K ℓn -free graphs of order n. Our proof is based on the recent hypergraph container theorems of Saxton, Thomason and Balogh, Morris, Samotij, in combination with a theorem of Lovász and Simonovits.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…It may well be the case that this supremum is equal to 1, though we are not prepared to state this as a conjecture. Theorem 1.1 improves a recent result of Mousset, Nenadov and Steger [20], who showed that, for the same 3 family of functions r = r(n), the number of n-vertex K r+1 -free graphs is…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…It may well be the case that this supremum is equal to 1, though we are not prepared to state this as a conjecture. Theorem 1.1 improves a recent result of Mousset, Nenadov and Steger [20], who showed that, for the same 3 family of functions r = r(n), the number of n-vertex K r+1 -free graphs is…”
Section: Introductionsupporting
confidence: 81%
“…3 In fact, a very slightly weaker theorem was stated in [20], but a little additional case analysis easily gives the result for all r (log n) 1/4 . 4 Similarly, we say that G is t-close to being r-partite if it is not t-far from being r-partite.…”
Section: Introductionmentioning
confidence: 97%
“…The proof of Theorem 7 uses our hypergraph containers theorem for L-structures (Theorem 6) and a powerful generalization by Aroskar and Cummings [5] of the triangle removal lemma (Theorem 10). Our proof strategies for these theorems draw on a series of enumeration results for combinatorial structures which employ the hypergraph containers theorem, namely those in [14,17,30,32,39]. We will also define generalizations of extremal graphs (Definition 17) and graph stability theorems (Definition 19).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…While our proofs are inspired by and modeled on those appearing in [14,17,30,32,39], our results are more than just straightforward generalizations of existing combinatorial theorems. We use new tools called L H -templates (see Section 3) and an application of the hyergraph containers theorem to a hypergraph whose vertices and edges correspond to certain atomic diagrams (see Theorem 11).…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Below, we will make use of a version of the container theorem of [2,22], the way it was formulated by Mousset-Nenadov-Steger [18]. …”
Section: Lemma 34 Let S ⊂ V (H ) Have No Empty Columns and Contain Nmentioning
confidence: 99%